THE PROBLEM OF LANGUAGE TEACHERS IN ONLINE LEARNING DURING THE PANDEMIC AN ANALYSIS OF TEACHING DISCOURSE IN SCHOOLS - Ulinsa, Ulinsa; Rinaldi, Rinaldi; Oringo, Vincent (ppjbsip, 2021)
The problems in the research are how problematic language teachers are in online learning during the pandemic, and how to solve problems for Indonesian language teachers in online learning during the pandemic. The purpose of this study is to describe the problems of Indonesian language teachers in online learning during the pandemic and to describe problem solving solutions for Indonesian language teachers in online learning during the pandemic. This research is a qualitative descriptive research. This type of research does not have a comparison group. The subjects in this study were Indonesian language teachers at SMP and SMA Negeri 1 Ampibabo in Ampibabo village. Data collection in this study were questionnaires, interviews and documentation. The data from the evaluation were analyzed using qualitative data analysis methods. The results of this study are (1) Inadequate internet network access during the online learning process. (2) The teacher is a